2012
DOI: 10.1007/s00603-012-0277-3
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Failure Criteria Based on the Hoek–Brown Criterion

Abstract: (Hoek and Brown 1997;Hoek et al. 2002) for rock engineering applications has prompted a number of researchers to develop three-dimensional versions, in which the predicted major effective principal stress at failure is dependent on the intermediate effective principal stress, in addition to the parameters in the existing 2DHB failure criterion. Threedimensional versions of the 2DHB failure criterion have been proposed by Pan and Hudson (1988), Priest (2005) and Zhang and Zhu (2007). Zhang (2008) presented a ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…Based on a large number of rock triaxial test data and statistic analysis of test results, the Hoek–Brown (H-B) strength criterion was established in 1988 (Hoek and Brown, 1988), which can reflect the inherent properties of rock mass and can explain the influence of low stress zone, tensile stress zone, and minimum principal stress on the strength, so it can be applied to the description of anisotropic rock mass. Since then, a lot of scholars revised the H-B strength criterion and used it to deduce the constitutive model of rock damage, many achieved good results (Ma et al., 2013; Priest, 2012; Zhang et al., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Based on a large number of rock triaxial test data and statistic analysis of test results, the Hoek–Brown (H-B) strength criterion was established in 1988 (Hoek and Brown, 1988), which can reflect the inherent properties of rock mass and can explain the influence of low stress zone, tensile stress zone, and minimum principal stress on the strength, so it can be applied to the description of anisotropic rock mass. Since then, a lot of scholars revised the H-B strength criterion and used it to deduce the constitutive model of rock damage, many achieved good results (Ma et al., 2013; Priest, 2012; Zhang et al., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the Mohr-Coulomb failure criterion neglects the additional role of the intermediate principal stress on fault reactivation, and the results as derived from this method should be always interpreted with caution. In this regard, other failure criteria for intact rock such that do consider the intermediate principal stress in their formulation as the modified Lade 3D rock strength criterion (da Fontoura, 2012), three-dimensional failure criteria based on the Hoek-Brown criterion (Priest, 2012), or failure criteria for rocks based on true triaxial testing (Chang and Haimson, 2012) could be additionally considered. In what follows is a brief analysis of the simulation results based on the concept of a true triaxial failure mode.…”
Section: Failure Criterion Based On True Triaxial Testingmentioning
confidence: 99%
“…Extensive experimental, analytical, and numerical studies have demonstrated that σ 2 has a significant influence on the rock failure characteristics (Crawford et al, 1995;da Fontoura, 2012;Duan et al, 2017;Feng et al, 2019;Haimson, 2006;Ma & Haimson, 2016;Mogi, 1967;Mogi, 1971;Priest, 2012;Schöpfer et al, 2013;Wiebols & Cook, 1968;Zhang & Zhu, 2007). For a given constant σ 3 , σ 1 at the failure of a rock (i.e., σ 1, peak ) often increases with the increment of σ 2 to a maximum magnitude and then decreases to a value just greater than its conventional compressive strength (Cai, 2008;Feng et al, 2019;Pan et al, 2012).…”
Section: Introductionmentioning
confidence: 99%